Inter‐annual variability and long‐term trends in breeding success in a declining population of migratory swans. (26th February 2016) - Wood, Kevin A.; Newth, Julia L.; Hilton, Geoff M.; Nolet, Bart A.; Rees, Eileen C.
Abstract : Population declines among migratory Arctic‐breeding birds are a growing concern for conservationists. To inform the conservation of these declining populations, we need to understand how demographic rates such as breeding success are influenced by combinations of extrinsic and intrinsic factors. In this study we examined inter‐annual variation and long‐term trends in two aspects of the breeding success of a migratory herbivore, the Bewick's swan Cygnus columbianus bewickii, which is currently undergoing a population decline: 1) the percentage of young within the wintering population and 2) mean brood size. We used an information‐theoretic approach to test how these two measures of productivity were influenced over a 26 yr period by 12 potential explanatory variables, encompassing both environmental (e.g. temperature) and intrinsic (e.g. pair‐bond duration) factors. Swan productivity exhibited sensitivity to both types of explanatory variable. Fewer young were observed on the wintering grounds in years in which the breeding period (May to September) was colder and predator (Arctic fox) abundance was higher. The percentage of young within the wintering population also showed negative density‐dependence. Inter‐annual variance in mean swan brood size was best explained by a model comprised of the negative degree days during the swan breeding period, mean pair‐bond duration of all paired swans (i.e. mean pair duration), and an interaction between these two variables. In particular, mean pair duration had a strong positive effect on mean brood size. However, we found no long‐term directional trend in either measure of breeding success, despite the recent decline in the NW European population. Our results highlight that inter‐annual variability in breeding success is sensitive to the combined effects of both intrinsic and extrinsic factors.